Synchronous and Asynchronous Transmitter Release at Nicotinic Synapses Are Differentially Regulated by Postsynaptic PSD-95 Proteins - Neff, Robert A. (Society for Neuroscience, 2009)
The rate and timing of information transfer at neuronal synapses are critical for determining synaptic efficacy and higher network function. Both synchronous and asynchronous neurotransmitter release shape the pattern of synaptic influences on a neuron. The PSD-95 family of postsynaptic scaffolding proteins, in addition to organizing postsynaptic components at glutamate synapses, acts transcellularly to regulate synchronous glutamate release. Here we show that PSD-95 family members at nicotinic synapses on chick ciliary ganglion neurons in culture execute multiple functions to enhance transmission. Together, endogenous PSD-95 and SAP102 in the postsynaptic cell appear to regulate transcellularly the synchronous release of transmitter from presynaptic terminals onto the neuron while stabilizing postsynaptic nicotinic receptor clusters under the release sites. Endogenous SAP97, in contrast, has no effect on receptor clusters but acts transcellularly from the postsynaptic cell through N-cadherin to enhance asynchronous release. These separate and parallel regulatory pathways allow postsynaptic scaffold proteins to dictate the pattern of cholinergic input a neuron receives; they also require balancing of PSD-95 protein levels to avoid disruptive competition that can occur through common binding domains.